If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 5) = 16 Reorder the terms: 3(5 + 2x) = 16 (5 * 3 + 2x * 3) = 16 (15 + 6x) = 16 Solving 15 + 6x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 6x = 16 + -15 Combine like terms: 15 + -15 = 0 0 + 6x = 16 + -15 6x = 16 + -15 Combine like terms: 16 + -15 = 1 6x = 1 Divide each side by '6'. x = 0.1666666667 Simplifying x = 0.1666666667
| -64x/4= | | 0.006(x+3)=0.007x+0.016 | | 7t-7r=2r-12r+3t | | 6x-(3x+13)=14 | | 62=1.068a-18.39 | | 18x^2=23x+6 | | 7x(3+2x)= | | 7(7x-2)=31 | | 0.50x+0.05(4-x)=0.10(-25) | | -12y*4y= | | 5(3x+2)= | | 6(6+8)= | | x^2-7+12= | | 3*4m= | | 15*12= | | z^2+11z+18= | | 9x-8=6x+16 | | (5a+1)(9-5)+7=31 | | (2x+1)(3x+7)= | | 12x-19=9x+9 | | 6*77= | | 9x+1=73 | | -49*6= | | 7*16= | | x+.05x=10.23 | | Y^4-361=0 | | 6x+6-340+295x=30 | | X^2-5x+22= | | Y^4-360=0 | | 10*27= | | y^2+8y-33= | | 10=-.66(4x+5) |